The financial crisis in the German and English press: Metaphorical structures in the media coverage on Greece, Spain and Italy. (July 2014) - Bickes, Hans; Otten, Tina; Weymann, Laura Chelsea
The German media presentation of the so-called Greek financial crisis caused an unexpected uproar in Germany. An anti-Greek sentiment evolved and spread among German citizens and solidarity for crisis-hit Greece was mostly rejected. Public surveys revealed that many Germans even wanted Greece to exit the Eurozone immediately. This article highlights the crucial role of the media in shaping the negative public opinion. In 2010, a period which has lately been referred to as Greek bashing, the German press had discussed the Greek financial crisis heatedly and controversially. Europe's largest daily newspaper, BILD, published numerous reports that implicitly and explicitly constituted the myth of the corrupt and lazy Greeks in comparison to the hard-working Germans. In 2012, the crisis had spread much further, and not only Greece but other countries too were suffering from high debt, economic stagnation and unemployment. The news coverage became more moderate and conciliating and presented the dramatic social consequences for the respective population. This study highlights not only the development of the German media's tenor on the Greek crisis through time, but adds an international perspective and widens the view by comparing the media treatment of the different countries involved. Based on 122 online articles, the study methodologically focuses on the analysis of metaphorical language in the news coverage of three comparable international news magazines: SPIEGEL (Germany), The Economist (the UK) and TIME (the USA), and contrasts the representation of Greece with the depiction of larger indebted European countries like Spain and Italy. The analysis shows remarkable differences in the evaluation and presentation of the crisis, which can be linked to the degree of involvement of Germany, the UK and the USA in European policies.